Role of immune mechanisms in induction of HIV-1 broadly neutralizing antibodies - Verkoczy, Laurent (2011)
Although antibodies can be elicited by HIV-1 infection or immunization, those that are broadly neutralizing (bnAbs) are undetectable in most individuals, and when they do arise in HIV-1 infection, only do so years after transmission. Until recently, the reasons for difficulty in inducing such bnAbs have been obscure. Recent technological advances in isolating bnAbs from rare patients have increased our knowledge of their specificities and features, and along with gene-targeting studies, have also begun uncovering evidence of immunoregulatory roadblocks preventing their induction. One critical avenue towards developing an effective HIV-1 vaccine is to harness this emerging information into the rational design of immunogens and formulation of adjuvants, such that structural and immunological hurdles to routinely eliciting bnAbs can be overcome.